Physical and mathematical model of working process of jet ejector - V. I. Kuznetsov; V. V. Makarov; A. Yu. Shander (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
A refined physical model of the jet ejector working process has been compiled. On the basis of the refined physical model, a mathematical model has been developed that takes into account the exchange of work and heat between the ejected and ejected gases. Based on the solution of this mathematical model, it is possible to formulate a method for calculating the optimal geometric dimensions of the jet ejector to obtain the specified thermodynamic parameters and a method for calculating the characteristics of the jet ejector with known geometric dimensions. The effect of viscosity on energy exchange is shown. The agreement between the calculated and experimental data is satisfactory.